Beta2-agonists prevent Th1 development by selective inhibition of interleukin 12. - Panina-Bordignon, P (1997)
Interleukin 12 (IL-12) plays a central role in the immune system by skewing the immune response towards T helper 1 (Th1) type responses which are characterized by high interferon-gamma and low IL-4 production. In this report we present evidence that beta2-agonists inhibit IL-12 production by both human monocytes in response to lipopolysaccharide (LPS) and dendritic cells stimulated via CD40. Inhibition of IL-12 production is selective, as other cytokines produced by monocytes are unaffected. IL-12 inhibition is dependent on beta2-adrenoceptor stimulation and correlates with increased levels of intracellular cAMP. In conjunction with their ability to suppress IL-12 production, when beta2-agonists are added at priming of neonatal T lymphocytes, they inhibit the development of Th1-type cells, while promoting T helper 2 (Th2) cell differentiation. Further, the in vivo administration of a therapeutic dose of salbutamol results in the selective inhibition of IL-12 production by whole blood lymphocytes stimulated in vitro with LPS. These findings provide new insight into the immunological consequences of the clinical use of beta2-agonists and may suggest new approaches for the treatment of Th1-mediated diseases.